Varietal identification key of the cultivated yams (Dioscoreaca-yenensis / Dioscorearotundata complex) of Benin Republic - DANSI ANAGONOU, ALEXANDRE; Mignou, H. D.; ZOUNDJIHEKPON, JEANNE; Sangare, A.; Asiedu, R; Quin, M. (My University, 1998)
Based upon IBPGR (IPGRI) morphologic descriptors, 560 accessions of Benin Republic’s cultivated yams (Dioscorea cayenensis / Dioscorea rotundata complex) were morphologically characterized. Ninety morphotypes were identified and accessions were classified into 26 varietal groups according to their morphological similarities. To case the varietal identification within each varietal group, a practical identification key was constructed and a general directory of the Benin Republic cultivated yams belonging to the complex Dioscorea cayenensis / Dioscorea rotundata (Guinea yams) was prepared.
Keywords: Benin Republic; morphological characteristics; Yams; Dioscorea cayenensis – D. rotundata complex